Cayanikā : 1941-42 nāṃ "Kavitā"nāṃ uttama kavyono saṅgraha - Bhaṭṭa, Premaśaṅkara Harilāla, 1914-; Rahimā (SAMP early 20th-century Indian books project ;, 1942)
Anthology of modern poetry selected from Kavitā, 1941-1942.